Resources and outcome impact of routine availability of computed tomography perfusion. (8th February 2021) - Baggiano, A; Del Torto, A; Fusini, L; Guglielmo, M; Muscogiuri, G; Andreini, D; Mushtaq, S; Conte, E; Annoni, AD; Formenti, A; Mancini, ME; Guaricci, AI; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Stress computed tomography perfusion (Stress-CTP) is a functional technique that can be added to coronary computed tomography angiography (cCTA) to improve the management of patients with suspected coronary artery disease (CAD). Purpose: To determine the impact of routine availability of Stress-CTP added to cCTA in terms of downstream testing, radiation exposure and outcome in patients with high risk or known CAD. Methods: Patients symptomatic for chest pain, known for CAD, with previous revascularization or with increased pre-test likelihood of CAD, referred for clinically indicated cCTA with Stress-CTP were prospectively enrolled. Data regarding evaluability, overall radiation exposure, invasive and non-invasive downstream testing, hospitalizations, revascularizations, major adverse cardiac events (MACE) as unstable angina, non-fatal myocardial infarction and cardiovascular death after index test were collected at follow-up. Results: 263 consecutive patients were prospectively enrolled (mean age: 65 ± 9 years; male: 79%), of which 162 (62%) had previous revascularization. The mean follow-up was 323 ± 175 days. cCTA and Stress-CTP were fully evaluable in 95% and 99%, respectively. Obstructive CAD and inducible ischaemia were found in 170 (65%) and 129 (49%) subjects, respectively. No significant difference was found between patients with presence or absence of perfusion defects in terms of downstream non-invasive testing (p: 0.229), while patients with inducible ischaemia had more downstream invasive testing, increased overall radiation exposure, more hospitalizations for cardiovascular reasons and revascularization (all endpoints with p: < 0.001). No differences were detected between patients with inducible ischaemia treated with revascularization after index test and patients without inducible ischaemia, even if with obstructive CAD, treated medically in terms of MACE. Conclusions: Routine implementation of cCTA with Stress-CTP is associated with subsequent low rate of other non-invasive testing, low overall radiation exposure in case of negative Stress-CTP and good prognosis if clinical management is based on combined anatomical and functional information.